Challenges in Implementing Diversion for Child Offenders: A Case Study of the Malang Police Department - Maharani, Febrianika (Universitas Negeri Gorontalo, 2025)
Diverting children from the formal criminal justice system is imperative to safeguard their future and well-being. Indonesia’s Juvenile Criminal Justice System Act (UU SPPA) mandates diversion at every stage of the process for children in conflict with the law. However, diversion frequently fails due to legal conditions not being met, particularly the requirement of victim approval under Article 9(2). This empirical, socio-legal study examines the challenges of implementing diversion at the investigative stage in the Malang Police Department. Findings reveal that while the police adopt a restorative and child-friendly approach, diversion efforts often collapse due to disproportionate demands from victims’ families, who can block the agreement entirely. Such power imbalance risks obstructing restorative justice and may subject children to unnecessary stigmatization and incarceration. The study highlights an urgent need for legislative reform to prevent the misuse of victim consent as an absolute condition. It proposes an amendment to Article 9 to empower investigators and social officers to assess the fairness of victims’ demands relative to actual harm. This research contributes novel insight by exposing how legal rigidity enables the undermining of diversion’s restorative aims and suggests a statutory safeguard to restore balance. These findings are critical to promoting equitable justice for all parties while ensuring the best interests of the child.